A bride of convenience - Hedlund, Jody (Hedlund, Jody. Bride ships, 2020)
"In 1863, Upon discovering an abandoned baby, Pastor Abe Merivale cares for the infant along with Zoe Hart, one of the newly arrived bride-ship women. With mounting pressure to find the baby a home, they hastily marry - but soon realize their marriage of convenience is not so convenient after all"--Provided by publisher.